The midnight ride of Paul Revere - Longfellow, Henry Wadsworth, 1807-1882; Longfellow, Henry Wadsworth, 1807-1882.; Bing, Christopher H (Brooklyn, N.Y. : Handprint Books, 2001)
An illustrated version of the narrative poem which describes Paul Revere's midnight ride in 1775 to warn the people of the Boston countryside of an impending attack by the British
Fold-out facsimiles on front and back endpapers
Includes bibliographical references
Keywords: Revere, Paul, 1735-1818 -- Juvenile poetry; Lexington, Battle of, Lexington, Mass., 1775 -- Juvenile poetry